PROGRAMY OCHRONY I OPIEKI NAD ZABYTKAMI – NIEDOCENIONY ELEMENT POLSKIEGO SYSTEMU OCHRONY ZABYTKÓW - Andrzej Siwek (Ochrona Dziedzictwa Kulturowego, 2016)
Under the Act of 23 July 2003 on the Protection and Guardianship of Monuments, a coherent model for caring for historic monuments and sites on both central and local levels was introduced. This concept is intertwined with monitoring and flow of information. The system of managing documents is aimed at optimising actions pertaining to the protection of cultural heritage. As there is a clear hierarchy of these documents, which can also correlate with each other, there are sound reasons behind establishing a coherent protection policy – from municipal/communal level to the central one. National, regional, district, and municipal/communal programmes pertaining to care for historic monuments and sites are strategic tools which shape policy, direct actions towards specific aims, and reflect the will. In a number of cases, however, no programmes have ever been developed. Administrative and legal supervision is still the predominant model in the protection of monuments and sites. The period of 2003 - 2016 was the time to „become familiar” with the new tool applied in heritage protection and management. One should learn from these experiences and promote the idea of devising a coherent strategy aimed at protecting historic monuments and sites by implementing programmes on all administrative levels.